2017
DOI: 10.18632/oncotarget.16058
|View full text |Cite|
|
Sign up to set email alerts
|

Artocarpin, an isoprenyl flavonoid, induces p53-dependent or independent apoptosis via ROS-mediated MAPKs and Akt activation in non-small cell lung cancer cells

Abstract: Artocarpin has been shown to exhibit cytotoxic effects on different cancer cells, including non-small cell lung carcinoma (NSCLC, A549). However, the underlying mechanisms remain unclear. Here, we explore both p53-dependent and independent apoptosis pathways in artocarpin-treated NSCLC cells. Our results showed that artocarpin rapidly induced activation of cellular protein kinases including Erk1/2, p38 and AktS473. Inhibition of these protein kinases prevented artocarpin-induced cell death. Moreover, artocarpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 59 publications
5
33
0
1
Order By: Relevance
“…High endogenous ROS concentrations in malignant cells may also render these cells more vulnerable to further stresses (34,39,40). Hence, anticancer therapies that trigger a further increase in ROS formation may induce cell death in cancer cells compared with their non-malignant counterparts (34,41,42). In addition, ROS can limit malignant growth by triggering activation of p53, whereas antioxidants enhanced tumor progression in a p53-dependent manner (17).…”
Section: Gr1mentioning
confidence: 99%
“…High endogenous ROS concentrations in malignant cells may also render these cells more vulnerable to further stresses (34,39,40). Hence, anticancer therapies that trigger a further increase in ROS formation may induce cell death in cancer cells compared with their non-malignant counterparts (34,41,42). In addition, ROS can limit malignant growth by triggering activation of p53, whereas antioxidants enhanced tumor progression in a p53-dependent manner (17).…”
Section: Gr1mentioning
confidence: 99%
“…Erastin-induced ferroptotic cell death is dependent on the increased level of intracellular reactive oxygen species (ROS), which are widely believed to act as a mediator of apoptosis. Tsai et al (8) found that, in A549 non-small cell lung cancer cells, the activation of p53-dependent apoptotic proteins, including PUMA, cytochrome c, Apaf-1 and caspase-3, was dependent on the presence of ROS. Accumulated ROS were also reported to regulate the expression and activation of p53, and the ROS/p53 pathway was found to regulate several cellular physiological processes, including cell senescence (9), oxidative protection (10) and apoptosis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Artocarpin, another flavonoid, is isolated from Artocarpus species such as Artocarpus heterophyllus , which is found in Southeast Asia and has long been used in agriculture, food, and traditional medicine. Artocarpin exerts anticancer activity by mediating apoptosis via ROS induction and suppression of the p38 MAPK, ERK1/2, and Akt signaling pathways in lung cancer cells (Tsai et al, ). Several studies have suggested that the MAPK and PI3K/Akt (phosphoinositide 3‐kinase/protein kinase B) pathways are targets for flavonoid‐mediated apoptosis.…”
Section: Natural Product‐derived Compounds As Potent Inducers Of Cellmentioning
confidence: 99%
“…Oxidative stress caused by this compound diminished ERK1/2 and p38 MAPK signaling, contributing to p53 activation and subsequently promoting PUMA expression and stimulating caspase‐3 cleavage. The latter mechanism was involved with inhibition of Akt phosphorylation, which in turn mediates NF‐κB, an upstream regulator of the c‐Myc and Noxa pathways (Tsai et al, ).…”
Section: Natural Product‐derived Compounds As Potent Inducers Of Cellmentioning
confidence: 99%